(untitled) (Bulletin KNOB, 2000)
In 1996 a building-historical study was made of Oudegracht 288. The present building mass was created in three phases. The oldest, one-layer brick phase was dated in approximately 1325, because of the combination of composite joisting and an attic without parapet. No traces of a kitchen fireplace dating from this phase were found, so that it is assumed that a wooden rear annex belonged to it. In the second phase, roughly around 1400, a cellar is added under the front part of the house, probably with a wharf cellar and the house is provided with a truss roof with parapet. The rear annex is rebuilt in brick and provided with an entresol. In the third phase, dated in approximately 1500 because of the application of timber corbels, all the woodwork is replaced. Two side extensions are also added, whereby the rear extension and the rear annex get cellars. The main house acquires an upper floor, a new truss roof with principal rafters partly placed in the parapet and a loft. In less than 200 years’ time the surface area for storage became six times larger through these additions. Consequently, Oudegracht 288 is a classic example of the development of an average house with some storage space into an average merchant’s house. The method of enlargement in depth, width and height are typical for medieval house building in Utrecht. An important aspect here is that the site of these types of houses initially covered the full depth of the building block, in Utrecht usually about 100 metres. Thus in a few centuries an uninterrupted ribbon of merchant’s houses arose along Oudegracht. The layout of these merchant’s houses is strikingly similar, regardless of their external appearance. Because of the possibility to unload merchandise from the ship to the wharf cellar, the ground floor in Utrecht hardly needed to be used for storage. The upper floors and attics, just as the cellars, were almost exclusively used for storage. The residents lived in the rear part of the house. The calculation of the surface area of the storage space used in this study seems to be a good method to compare merchant’s houses in various towns with divergent urban-planning situations and therefore different possibilities for enlargement.